Genetic Variation in Antimicrobial Activity of Honey Bee (Apis mellifera) Seminal Fluid - Holt, Shannon; Cremen, Naomi; Grassl, Julia; Schmid-Hempel, Paul; Baer, Boris (Frontiers in Ecology and Evolution, 2021)
Honey bees can host a remarkably large number of different parasites and pathogens, and some are known drivers of recent declines in wild and managed bee populations. Here, we studied the interactions between the fungal pathogen Nosema apis and seminal fluid of the Western honey bee (Apis mellifera). Honey bee seminal fluid contains multiple antimicrobial molecules that kill N. apis spores and we therefore hypothesised that antimicrobial activities of seminal fluid are genetically driven by interactions between honey bee genotype and different N. apis strains/ecotypes, with the virulence of a strain depending on the genotype of their honey bee hosts. Among the antimicrobials, chitinases have been found in honey bee seminal fluid and have the predicted N. apis killing capabilities. We measured chitinase activity in the seminal fluid of eight different colonies. Our results indicate that multiple chitinases are present in seminal fluid, with activity significantly differing between genotypes. We therefore pooled equal numbers of N. apis spores from eight different colonies and exposed subsamples to seminal fluid samples from each of the colonies. We infected males from each colony with seminal fluid exposed spore samples and quantified N. apis infections after six days. We found that host colony had a stronger effect compared to seminal fluid treatment, and significantly affected host mortality, infection intensity and parasite prevalence. We also found a significant effect of treatment, as well as a treatment x colony interaction when our data were analysed ignoring cage as a blocking factor. Our findings provide evidence that N. apis-honey bee interactions are driven by genotypic effects, which could be used in the future for breeding purposes of disease resistant or tolerant honey bee stock.